The discursive framework of sustainability in UK food policy: the marginalised environmental dimension. Issue 4 (3rd July 2020) - Ehgartner, Ulrike
ABSTRACT: In the context of food policy, sustainability functions as a normative principle but also constitutes a highly contested arena. The study presented in this paper establishes how discursive dynamics amongst professionals involved in matters of food distribution, retail, consumption and waste lead to food policy themes being framed as issues of sustainability. Analysing varied UK-based data (trade magazine articles, policy documents and interviews with retail, non-profit and consultancy representatives), three interpretative frames of sustainability are identified: consumer sovereignty, economic rationality and stewardship. Focusing on three themes of food sustainability – organic consumption, protein diversity and waste reduction – it is shown how these interpretative frames constitute the discursive framework relevant to food policy. Based on these findings, it is shown how in the analysed debates environmental concerns are sidelined.